KUANTITAS UJI KOMPETENSI GURU MATEMATIKA SEKOLAH MENENGAH PERTAMA DI KABUPATEN BANGKA TENGAH TAHUN 2015 - Vika Martahayu; Ayen Arsisari (Prosiding Simposium Nasional Multidisiplin (SinaMu), 2019)
Abstract This research is about the first description of the quantity of competency testing of mathematics teachers at school level in Central Bangka district. The purpose of this study is to find out. (1) Description of teacher competency, especially pedagogical competence and professional competence of junior high school mathematics teachers in middle bangka kabutan who have taken UKG; (2) constraints of junior high school math teachers in taking UKG. This research method uses quantitative descriptive methods. Data sources are primary data sources in the form of informant words and secondary data sources in the form of UKG 2015 documentation and archives. The sampling technique uses purposive sampling. Data collection techniques use documentation, questionnaires and interviews. The results of this study can be concluded that: (1) Pedagogical and professional competence of junior high school mathematics teachers in Bangka Tengah district itself is good but still needs to be improved. This can be seen from the results of (a) pedagogical and professional competencies have been implemented as indicators of Minister of Education Regulation No. 16 of 2007 (b) the average value of UKG on pedagogic competence is 66.29 and professional competence is 66.04 (2) The obstacles faced in taking UKG are the material tested on his professional competence is too broad, lack of mastery of pedagogical competencies, lack of some teachers have mastery of computers. Keywords: pedagogic competence, professional competence, mathematics teacher competency test